Estado trófico de la laguna San Miguel del Monte (Pdo de San Miguel del Monte, Buenos Aires) - Gabellone, Nestor Adrian (2000)
The purpose'of this paper was to determine the trophy status of San Miguel del Monte pond because eutrophication produces increase of turbidity, depletion of dissolved oxygen and alteration of aquatic communities) and the consequent decrease of water quality. The samples were taken monthly (9197-8198) analysing physical and chemical characteristics of water and plankton community. The trophic status was determined by means index, planktonic structure and the presence of biological indicators. Maximum TSI values (9197) of total phosphorus and transparency were 95 and 83, respectively. At the next month, an aquatic macrophyte occupied the entire basin and competed with planktonic algae for the phosphorus comsuption. In consequence, the TSI of total phosphorus and transparency decreased to minimum values of 73 and 70, respectively (61 98), representing a mesotrophic condition. Nevertheless, trophic evaluation by means planktonic structure (Shannon & Weaver index) differed with TSI determinations because in these occasions similar diversity values were obtained. The plankton community was complex (100 species) unexpected in eutrophic conditions. Regional indicators and regional index must be applied for fbture trophic evaluations of pampean ponds instead the use of trophic index with boreal hemispheric origin.